Neuropsychological and biopsychosocial evolution, therapeutic adherence and unmet care needs during paediatric transplantation: study protocol of a mixed-methods design (observational cohort study and focus groups) – the TransplantKIDS mental health project - Garrido-Bolton, Jessica; Alcamí-Pertejo, Margarita; de la Vega, Rocío; Hernández-Oliveros, Francisco; Pérez-Martínez, Antonio; Bravo-Ortiz, María Fe; Fernández-Jiménez, Eduardo (Frontiers in Psychology, 2024)
The present article describes the protocol of a mixed-methods study (an observational cohort design and focus groups), aimed to examine neuropsychological functioning and other biopsychosocial outcomes, therapeutic adherence and unmet care needs in paediatric population undergoing solid organ or allogeneic hematopoietic transplant during the pre- and post-transplant phases. Following a multi-method/multi-source approach, neuropsychological domains will be comprehensively measured with objective tests (SDMT, K-CPT 2/CPT 3, TAVECI/TAVEC, WISC-V/WAIS-IV Vocabulary and Digit Span subtests, Verbal Fluency tests, Stroop, ROCF, and TONI-4); ecological executive functioning, affective and behavioral domains, pain intensity/interference, sleep quality and therapeutic adherence will be assessed through questionnaires (parent/legal guardians-reported: BRIEF-2 and BASC-3; and self-reported: BASC-3, BPI, PROMIS, AIQ and SMAQ); and blood levels of prescribed drugs will be taken from each patient’s medical history. These outcomes will be measured at pre-transplant and at 4-weeks and 6-months post-transplant phases. The estimated sample size was 60 patients (any type of transplant, solid organ, or hematopoietic) from La Paz University Hospital (Madrid, Spain). Finally, three focus group sessions will be organized with patients, parents/guardians, and transplant clinicians (n = 15, with 5 participants per group), in order to qualitatively identify unmet care needs during the pre-, and post-transplant stages of the process. The study protocol was registered at ClinicalTrials.gov (NCT05441436).